Hadith #3068 - Sunan Abi Dawud - Abu Bakr bin 'Ayyash al-Asadi أبو بكر بن عياش بن سالم الأسدي; al-Husain bin 'Ali bin al-Walid al-Ja'fi الحسين بن علي بن الوليد الجعفي; Asma' bint Abi Bakr; Hisham bin 'Urwa هشام بن عروة; Urwa ibn al-Zubayr عروة بن الزبير; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان (Sunan Abi Dawud)
The Prophet (ﷺ) alighted at a place where a mosque has been built under a large tree. He tarried there for three days, and then proceeded to Tabuk. Juhaynah met him on a wide plain. He asked them: who are the people of Dhul-Marwah? They replied: Banu Rifa’ah of Juhaynah. He said: I have given this (land) to Banu Rifa’ah as a fief. Therefore, they divided it. Some of them sold (their share) and others retained and worked on it. (Sub-narrator Ibn Wahab said: I then asked AbdulAziz about this
Grade: Hasan

Hadith #3322 - Sunan Abi Dawud - Abu Bakr bin 'Ayyash al-Asadi أبو بكر بن عياش بن سالم الأسدي; Ka'b bin 'Alqama bin Ka'b كعب بن علقمة بن كعب; Marthad bin 'Abdullah al-Yazni مرثد بن عبد الله اليزني; Uqba bin 'Amir al-Juhayni (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone takes a vow but does not name it, its atonement is the same as that for an oath, if anyone takes a vow to do an act of disobedience, its atonement is the same as that for an oath, if anyone takes a vow he is unable to fulfill, its atonement is the same as that for an oath, but if anyone takes a vow he is able to fulfill, he must do so. Abu Dawud said: This tradition has been transmitted by Waki’ and others on the authority of ‘Abd Allah b. Sa’id b. Abi al-
Grade: Hasan

Hadith #4012 - Sunan Abi Dawud - Abdul Malik bin Aby عبد الملك بن أبي سليمان; Abu Bakr bin 'Ayyash al-Asadi أبو بكر بن عياش بن سالم الأسدي; al-'Aswad bin 'Amir Shadhan الأسود بن عامر شاذان; Ata' bin Abi Rabah عطاء بن أبي رباح; Muhammad bin Ahmed bin Abi Khalaf محمد بن أحمد بن أبي خلف; Safwan bin Y'ala bin Umayya صفوان بن يعلى بن أمية; Ya'la bin Umayya (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) saw a man washing in a public place without a lower garment. So he mounted the pulpit, praised and extolled Allah and said: Allah is characterised by modesty and concealment. So when any of you washes, he should conceal himself.
Grade: Sahih

Hadith #4090 - Sunan Abi Dawud - Abu Bakr bin 'Ayyash al-Asadi أبو بكر بن عياش بن سالم الأسدي; Alqama bin Qays علقمة بن قيس بن عبد الله; ibn Mas'ud; Ibrahim al-Nakha'i إبراهيم النخعي; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
The Prophet (ﷺ) said: Allah Most High says: Pride is my cloak and majesty is my lower garment, and I shall throw him who view with me regarding one of them into Hell.
Grade: Sahih

Hadith #4281 - Sunan Abi Dawud - Abu Bakr bin 'Ayyash al-Asadi أبو بكر بن عياش بن سالم الأسدي; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Ahmed bin Ibrahim bin Kathir أحمد بن إبراهيم بن كثير; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ubaidullah bin Musa bin Abi al-Mukhtar عبيد الله بن موسى بن أبي المختار باذام; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان; Za'ida bin Qadama al-Thaqifi زائدة بن قدامة الثقفي (Sunan Abi Dawud)
When he came back to his home. the Quraish came to him and said: Then what will happen ? He said: Then turmoil will prevail.
Grade: Sahih

Hadith #4878 - Sunan Abi Dawud - Abu Bakr bin 'Ayyash al-Asadi أبو بكر بن عياش بن سالم الأسدي; Abu Burzah al-Aslami; al-'Aswad bin 'Amir Shadhan الأسود بن عامر شاذان; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Uthman bin Muhammad (Sunan Abi Dawud)
The Prophet (ﷺ) said: When I was taken up to heaven I passed by people who had nails of copper and were scratching their faces and their breasts. I said: Who are these people, Gabriel? He replied: They are those who were given to back biting and who aspersed people’s honour. Abu Dawud said: Yahya b. ‘Uthman has also transmitted it from Baqiyyah, there is no mention of Anas in it.
Grade: Sahih